WOMEN'S PARTICIPATION IN DEVELOPMENT: A CASE STUDY IN UPPKA KARTIKA BERLIAN, LAKSAMANA VILLAGE, DUMAI CITY - Mukhammad Fatkhullah; Iwed Mulyani; Muhammad Alhada Fuadilah Habib (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
This research examines the participation and strategies of the women's community in Laksamana Village in developing UPPKA (Acceptor Family Income Increase Program) Kartika Berlian. This research uses a descriptive qualitative method. Data collection used in-depth interview techniques on 15 subjects consisting of UPPKA members, Kampung KB cadres, BKKBN assistants, village staff, and sponsor company field facilitators. The analysis was done by reducing the data, categorizing it into relevant topics, presenting it in narrative descriptions, and formulating conclusions. The results showed that UPPKA Kartika Berlian became a forum for the women's community in Laksamana Village to actualize themselves, meet their daily needs, and even encourage the wheels of the economy to replace the role of men. The strategy to support this effort is establishing partnerships with various stakeholders such as government agencies, State-Owned Enterprises (BUMN), and private companies to obtain financial assistance, infrastructure development, skills training, and various outreach activities.